Answer:
The first two are equivalent but different than the third.
Explanation:
![8n+6 = 2(4n+3) => 6=6\\8n+6 = 14n => 6n = 6 => n = 1\\\\](https://img.qammunity.org/2022/formulas/mathematics/middle-school/bz3figjpzi4falhahoasyosvu14pkjgg07.png)
The first two are identical by factoring 2 out of the first one, or distributing 2 in the second one.
The equality of the first and third equations, suggests that it is only true for n = 1.
To prove it wrong, find a number that shows the inequality:
![n = 2\\8n+6 = 2(4n+3) = 22\\14n = 28\\\\22 \\eq 28](https://img.qammunity.org/2022/formulas/mathematics/middle-school/6yhnko6gr4g3goqs26dm6bhf612121d3be.png)